Management of the Pediatric Patient with Suspected Diagnosis of Obstructive Sleep Apnea Syndrome - Sorina Savin; Luca Mezzofranco; Antonio Gracco; Giovanni Bruno; Alberto De Stefani (MDPI AG, 2023)
Aim: The aim of this paper is to describe the multidisciplinary management pathway for pediatric patients with suspected obstructive sleep apnea syndrome (OSAS) conducted by the Pediatric and Orthodontic Department of the Dental Clinic of Padua. Materials and methods: All pediatric subjects undergo a comprehensive medical history, including the completion of the Pediatric Sleep Questionnaire (PSQ), and a physical examination. Patients with suspected OSAS are placed on a waiting list for home respiratory polygraphy testing. The respiratory polygraphy examination is conducted over two consecutive nights and interpreted by a neurologist. Additionally, patients diagnosed with OSAS undergo a case study involving intraoral and extraoral photography, as well as radiographic evaluation. Results: Between September 2021 and May 2023, a total of 134 subjects (including 76 males), with an average age of 9.2 years, were identified as diagnostic suspects. Among these, 38 patients (28.3%) tested positive based on respiratory polygraphic results. Depending on the severity and etiopathogenetic characteristics of the disease, the positive cases were referred to various specialists. Conclusion: In the daily clinical practice of dentistry, particularly in orthodontics and pedodontics, the establishment of a defined management pathway for pediatric patients with OSAS is crucial. The collaboration of a multidisciplinary team with a shared objective of achieving accurate diagnosis and implementing targeted treatment in a timely manner is essential. Regular re-evaluation of patients through clinical and instrumental examinations is recommended.